Associationbetween hyperoxia and mortality in severely burned patients. Issue 6 (September 2020) - Halgas, B.; Bay, C.; Neagoe, A.; Richey, K.; Hofmann, L.; Foster, K.
Highlights: Hyperoxia is common and not yet studied in a burn population. Hyperoxia is generally defined in literature as serum PaO2 greater than 300 mm Hg. There are few guidelines on when and how to use oxygen in acute burn resuscitation. We found an association between hyperoxia and mortality in severely burned patients. Only a small minority of patients had confirmed carbon monoxide toxicity. Abstract: Introduction: The use of oxygen is a key component of acute burn resuscitation, particularly when there is concern for carbon monoxide toxicity or inhalation injury. Prior studies of critically-ill patients have shown an association between early hyperoxia and increased mortality. There are no studies to date evaluating outcomes related to excessive oxygen administration in burn patients. Methods: We conducted a retrospective analysis of 219 severely burned patients to quantify the average amount of oxygen given during initial resuscitation, the level of carbon monoxide exposure, and to determine if early exposure to supratherapeutic oxygen was associated with increased hospital mortality or ventilator-associated pneumonia (VAP). The models were adjusted for inhalation injury and total body surface area (TBSA) burned. Results: Early hyperoxia in severely burn patients is common and possibly associated with increased overall mortality, although the results were inconclusive and after adjusting for burn-specific scoring systems, we found a negative correlation between hyperoxia and mortality. Confirmed carbon monoxide poisoning was relatively uncommon, but also associated with increased mortality. Patients with elevated carboxyhemoglobin did not receive more oxygen compared to others within the cohort. Conclusions: Burn patients are exposed to higher concentrations of pure oxygen compared to other critically-ill patients, presumably for empiric treatment of carbon monoxide poisoning. Our data showed a liberal use of oxygen therapy across all patients. Considering the potentially negative effects of hyperoxia, this study exposes either a gap in clinical research or need for clearer indications.